After London: securing public transport systems against terrorist attacks - Acharya, Arabinda (2016)
THE bombings in London underscore the vulnerability of underground transport systems to terrorist attacks in large cities where millions of passengers commute daily. Following the incidents in London, many other countries in Europe and elsewhere have taken steps to bolster security on their respective domestic transport systems, including underground rail networks and airports. The enhanced security measures include the deployment of additional security personnel, sniffer dogs as well as increased vigilance by the crew who run or man the systems. The question remains, however, whether the measures would be adequate to secure the systems against possible future terrorist attacks.